Students’ Feelings of Using Figurative Language in Creating Poems at Creative Writing Class: A Narrative Inquiry - Fitriana, Ana; Rokhuma, Chubbi Millatina (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
Figurative language is a vital element in poetry that allows writers to express emotions, ideas, and imagery in creative and impactful ways. In the context of creative writing classes, especially poetry writing, students are encouraged to explore and utilize various figurative expressions to enhance the depth and beauty of their compositions. However, considering its complexity, the use of figurative language in writing a poem can create a range of emotions. This study aims to identify and understand students' emotional experiences in a creative writing class using figurative language at a university in Pekalongan. A qualitative method was employed through narrative inquiry to explore how students in a creative writing class experienced the use of figurative language while composing poems. The researchers used semi-structured interviews to collect data. The data were analyzed using the Miles, Huberman & Saldana analysis method. The participants of this study were students majoring in English department who had created poems using figurative language in creative writing class. The results of this study revealed some positive feelings felt by the students, such as excitement, happiness, interest, pride, and satisfaction. On the other hand, negative feelings felt by students include anxiety, frustration, and boredom. This study contributes to a deeper understanding of students' emotional experiences so that it can offer valuable insights for choosing appropriate teaching methods and media in teaching poems using figurative language in creative writing class.